HIV care cascade and associated factors among men who have sex with men, transgender women, and genderqueer individuals in Zimbabwe: findings from a biobehavioural survey using respondent-driven sampling. Issue 3 (March 2022) - Harris, Tiffany G; Wu, Yingfeng; Parmley, Lauren E; Musuka, Godfrey; Mapingure, Munyaradzi P; Chingombe, Innocent; Mugurungi, Owen; Hakim, Avi; Gozhora, Perpetua; Miller, Sophia S; Lamb, Matthew R; Samba, Chesterfield; et al.
Summary: Background: Globally, men who have sex with men (MSM), transgender women, and genderqueer individuals are at greater risk for HIV than the general population although little data are available from these groups in Zimbabwe, a country with a national adult HIV prevalence of 12·9%. We aimed to examine progress towards the UNAIDS 90–90–90 treatment targets and factors associated with meeting the targets among a sample of MSM, transgender women, and genderqueer individuals in Zimbabwe. Methods: In this cross-sectional survey in 2019, we used respondent-driven sampling to identify MSM, transgender women, and genderqueer individuals aged at least 18 years to participate in a biobehavioural survey in Harare and Bulawayo, Zimbabwe. Participants were eligible to participate if they were assigned male at birth; had engaged in anal or oral sex with a man in the past 12 months; resided in Harare or Bulawayo for at least 1 month; spoke English, Shona, or Ndebele; provided written informed consent; and were in possession of a valid recruitment coupon if applicable. Enrolled participants completed a questionnaire and underwent HIV testing, and off-site viral load testing was done on all HIV-positive samples. Unweighted bivariate analyses and multivariable logistic regression models were used to evaluate the association of sociodemographic, behavioural, and other factors with HIV-positive status awareness among MSM, transgender women, and genderqueer individuals, and with viral load suppression among MSM. Analyses were done firstly using self-reported information and then by classifying those with a viral load of less than 200 copies per mL as being aware of their status and on treatment (viral load recategorisation). Findings: Among MSM, 248 (21%; 95% CI 19–24) of 1176 tested positive for HIV. Of those who tested positive, based on self-report, 119 (48%; 95% CI 42–54) reported knowing their HIV status, of whom 112 (94%; 88–98) reported using antiretroviral therapy (ART), of whom 89 (79%; 71–87) had viral load suppression. Based on viral load recategorisation, 180 (73%; 67–78) of 248 MSM testing HIV positive reported knowing their HIV status, of whom 174 (97%; 93–99) reported using ART, of whom 151 (87%; 81–91) had viral load suppression. 92 (28%; 23–33) of 335 transgender women and genderqueer individuals tested positive for HIV. Based on self-reports from these individuals 34 (37%; 27–48) of 92 participants reported knowing their HIV status, of whom 31 (91%; 76–98) reported using ART, of whom 27 (87%; 70–96%) had viral load suppression. Based on viral load recategorisation of data from transgender women and genderqueer participants, 53 (58%; 47–58) of 92 reported awareness of their HIV status, of whom 50 (94%; 84–99) reported using ART, of whom 46 (92%; 81–98) had viral load suppression. HIV-positive MSM aged 18–24 years had lower odds of being aware of their status than those aged at least 35 years (adjusted odds ratio [aOR] 0·34; 95% CI 0·13–0·92), as did HIV-positive MSM aged 25–34 years (aOR 0·26; 0·12–0·56). HIV-positive MSM aged 18–24 years also had a lower odds of having viral load suppression than those aged 35 years and older (aOR 0·35; 0·16–0·78), as did those aged 25–34 years (aOR 0·36; 0·19–0·67). No factors were significantly associated with awareness among transgender women and genderqueer individuals in multivariable models. Interpretation: Our survey showed that HIV prevalence was high and the largest difference between our results and the 90–90–90 treatment targets was in HIV status awareness, indicating the need for improvements in engaging MSM (especially young MSM), transgender women, and genderqueer individuals in HIV testing services. Funding: US President's Emergency Plan for AIDS Relief through the US Centers for Disease Control and Prevention.